2023
DOI: 10.2147/dddt.s405450
|View full text |Cite
|
Sign up to set email alerts
|

UBE2T Promotes Temozolomide Resistance of Glioblastoma Through Regulating the Wnt/β-Catenin Signaling Pathway

Abstract: Purpose Patients with glioblastoma (GBM) have poor prognosis and limited therapeutic options, largely because of chemoresistance to temozolomide (TMZ) treatment. Ubiquitin conjugating enzyme E2 T (UBE2T) plays a key role in regulating the malignancy of various tumors, including GBM; however, its role in TMZ resistance of GBM has not been elucidated. The purpose of this study was to clarify the role of UBE2T in mediating TMZ resistance and investigate the specific underlying mechanism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In addition, an association between the WNT signaling pathway and OSCC prognosis has been established [ 45 52 ], positioning it as an independent prognostic factor [ 16 , 53 , 54 ]. The role of WNT/β-catenin activation in mediating chemoresistance in other cancers has also been confirmed in the emerging literature [ 18 , 55 , 56 ], in which WNT/β-catenin activation supports 5FU-resistance through mechanisms such as cancer stem cell, metastasis, and enhanced transcriptional activity [ 19 , 57 59 ].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition, an association between the WNT signaling pathway and OSCC prognosis has been established [ 45 52 ], positioning it as an independent prognostic factor [ 16 , 53 , 54 ]. The role of WNT/β-catenin activation in mediating chemoresistance in other cancers has also been confirmed in the emerging literature [ 18 , 55 , 56 ], in which WNT/β-catenin activation supports 5FU-resistance through mechanisms such as cancer stem cell, metastasis, and enhanced transcriptional activity [ 19 , 57 59 ].…”
Section: Discussionmentioning
confidence: 85%
“…Although there have been many studies on the mechanism of 5FU-resistance, it still remains unclear. In recent years, the Wingless and Int-1 (WNT)/β-catenin signaling pathway has received more and more attention in the study of drug resistance [ 15 19 ]. The WNT/β-catenin pathway is activated by ligands such as WNT1, WNT3, WNT3A, WNT8A, WNT10A, and WNT10B, and then β-catenin enters the nucleus and binds to the transcription factor TCF/LEF, thus regulating the expression of downstream target genes such as c-Myc, cyclin D1, and AXIN2 [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition of the role of ubiquitination enzymes in chemotherapeutic resistance has been growing alongside the increasing number of studies conducted on these enzymes in various cancers. A notable example is the promotion of resistance to cisplatin in non-small cell lung cancer through TRIM17-mediated ubiquitination and degradation of RBM38 (Zhong et al 2023 );RNF6 promotes cisplatin resistance by transcriptionally activating the expression of proliferating cell nuclear antigens and attenuating DNA damage in lung adenocarcinoma (Sun et al 2022 ).In addition, UBE2T promotes temozolomide resistance in glioblastoma by modulating the Wnt/β-catenin signaling pathway (Wang et al 2023 ). The results of these experiments may provide insights into the mechanisms of chemoresistance of these ubiquitination enzymes in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a high-throughput small interfering RNA (siRNA) screen in T98G glioma cells reported that 22% of the genes identified as being crucial for GB survival encoded for components of the proteasome subunits 20S and 26S [36]. Moreover, aberrant levels of different E2 and E3 enzymes have been reported in glioma, having either oncogenic or antitumoral effects [37][38][39][40]. On the other hand, altered levels of deubiquitinating enzymes (DUBs), which enhance protein stability by cleaving the ubiquitin and thus reversing ubiquitinmediated proteolysis, can also affect crucial signaling pathways and consequently lead to malignancies.…”
Section: Ube2c 21 Ubiquitin Proteasome Systemmentioning
confidence: 99%